Gender Strategies In Principal Leadership on Teacher Performance Satisfaction At SMP 35 Medan School - Rina Siregar, Asma; Syukri, Makmur (Dinasti International Journal of Economics, Finance & Accounting, 2024)
SMP 35 Medan is a formal, non-formal and informal educational institution established by public and private parties. Its purpose is to teach, manage and educate educators or teachers. In teaching and learning activities, the school's goal is to educate students under the supervision of teachers. School quality is highly dependent on the learning process, which can be supported through the provision of facilities by schools, both in physical form (facilities and infrastructure) and the competence of teaching staff. This study aims to determine the effect of principal leadership on teacher performance satisfaction at SMP 35 Medan. This research covers the principal's strategy as a leader, principal leadership, teacher performance satisfaction, as well as views on gender strategy in principal leadership on teacher performance satisfaction. This research uses qualitative methods with interview techniques, observation, and documentation studies as well as observing every activity of the principal. The results showed that planning is done with several stages and considerations. The performance of principals and teachers can be seen from the way they guide education in schools.